Complete Urogenital and Anorectal Duplication in a Dog. (3rd March 2019) - Coffman, Jonathan M.; McConkey, Marina; Ellison, Gary; Huynh, Elizabeth; Dark, Michael J.
Abstract : A 10-week-old sexually intact female golden retriever was evaluated for two functional anal openings and a bipartite vulva. Examination revealed haired skin between two separate anatomically smaller anal openings. On rectal palpation, a soft tissue septum (5 cm) with a mucosal surface between the two anal openings was palpated. In addition, circumferential rectal musculature was not appreciated on the ventral aspect. Urogenital evaluation revealed duplication of the vestibule and vagina with a complete centrally located septum extending dorsoventrally. Computed tomography (CT) of the abdomen and pelvis, vaginocystourethrogram, and colonogram were performed. Complete bifurcation of the urinary bladder with duplication of the urethra, cervix, and vaginal canal was noted. Approximately 2 cm from the rectum, there was a similar bifurcation that converged the colon into two rectal portions and separate anal openings. The owner was counseled on the severity of congenital malformations and a high likelihood of aging-related developmental complications in the future. The owner elected humane euthanasia and a necropsy was performed to confirm the malformations.